Nonlinear scale-space based boundary localization for nonideal iris - Hong-lin WAN; Bao-sheng LI; Min HAN; Deng-wang LI (Tongxin xuebao)
A nonlinear scale-space based localization method of nonideal iris boundaries was proposed.The method eliminates small-scaled geometric structures while preserving large-scaled iris boundaries by nonlinear diffusions with the scale-evolution property.Moreover it combines such diffusions with the frame of multiresolution analysis,and achieves fast and effective iris boundary detection.Experimental results indicate that compared with the classical methods,the proposed algorithm extract nonideal iris boundaries accurately and efficiently with overcoming the disadvantageous influences of the nonideal factors.